2005
DOI: 10.1002/chem.200500465
|View full text |Cite
|
Sign up to set email alerts
|

Structure and IR Spectrum of Phenylalanyl–Glycyl–Glycine Tripetide in the Gas‐Phase: IR/UV Experiments, Ab Initio Quantum Chemical Calculations, and Molecular Dynamic Simulations

Abstract: We investigated the potential-energy surface (PES) of the phenylalanyl-glycyl-glycine tripeptide in the gas phase by means of IR/UV double-resonance spectroscopy, and quantum chemical and statistical thermodynamic calculations. Experimentally, we observed four conformational structures and we recorded their IR spectra in the spectral region of 3000-4000 cm(-1). Computationally, we investigated the PES by a combination of molecular dynamics/quenching procedures with high-level correlated ab initio calculations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
145
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(151 citation statements)
references
References 51 publications
4
145
0
2
Order By: Relevance
“…However, due to their computational cost, their applicability has been restricted to smaller systems such as amino acids, and di-and tripeptides. 5,6 Tetrapeptides are the smallest model systems that are able to mimic the typical hydrogen-bond pattern in a-helices. They are therefore of particular biological interest, and QM treatments of them have been reported since the late 1990s.…”
mentioning
confidence: 99%
“…However, due to their computational cost, their applicability has been restricted to smaller systems such as amino acids, and di-and tripeptides. 5,6 Tetrapeptides are the smallest model systems that are able to mimic the typical hydrogen-bond pattern in a-helices. They are therefore of particular biological interest, and QM treatments of them have been reported since the late 1990s.…”
mentioning
confidence: 99%
“…We have also covered the phenomena of halogen bonding 3 . Aside from noncovalent complexes, we have studied conformers of small peptides [4][5][6] at the same level of theory. This list is not final; we are working on more systematic high-level studies.…”
mentioning
confidence: 99%
“…Also, B3LYP/6-31+G(d) and MP2/6-31+G(d) calculations predicted markedly different structures for the tyrosilglycine (YG) dipeptide [21]. The same conformational behaviour discrepancy between these two methods was observed for a number of other molecules containing an aromatic ring in addition to a flexible side chain, WG [17][18][19] and WGG [18,19]. Further investigation suggested that the very different structures obtained by B3LYP and MP2 are likely caused by dispersion (a true physical effect, underestimated by B3LYP) as well as large basis set superposition errors (BSSE, an artificial attraction) in the MP2 calculations [22].…”
Section: Introductionmentioning
confidence: 90%
“…One of the most important reasons for this inaccuracy might be the fact that they work with effective average charges (over all existing structures), which may be far from the charges that properly describe each individual structure. It has recently been proven that the scan of the PES of FGG [17] and GFA [46] by using the AMBER empirical force field fails mainly due to a large variety of atomic charges for individual conformers. These calculations have demonstrated that introducing an average charge brings some uncertainty that results in incorrect structural predictions when an empirical potential is used.…”
Section: Conformational Study Of Ygg In Solutionmentioning
confidence: 99%
See 1 more Smart Citation